(3efM GdeOMs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s
(3ChdgG (B:s
(3hef Cde HgG aYGL eSdekG hHci Ydi CWdGdgG CaRJ (B[(3cPG(B] (3OeG s
(3Vef eLehY , JQJjHgG (B: (3ef U C (B55 - (3U H (B57s
(3JJVef CSeGA LeGYI ef GdUMGHI eef eOM GdfHi GhQKGgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B77 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B435 s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B((3) 3557) s
Keywords: (3GdJGQjNs